2020
DOI: 10.1093/sleepadvances/zpaa006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-channel EEG, actigraphy, and sleep diary in cognitively normal and mildly impaired older adults

Abstract: Study Objectives Multiple methods for monitoring sleep-wake activity have identified sleep disturbances as risk factors for Alzheimer disease (AD). In order to identify the level of agreement between different methods, we compared sleep parameters derived from single-channel EEG (scEEG), actigraphy, and sleep diaries in cognitively normal and mildly impaired older adults. Methods 293 participants were monitored at home for up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Ambulatory polysomnography, including EEG, could provide a more definitive differentiation of wake/sleep, provide additional information regarding sleep staging and depth, and identify some causes of sleep fragmentation (e.g., sleep apnea). While several studies have demonstrated the feasibility of ambulatory EEG in adults with mild dementia, 44,45 it remains challenging to obtain ambulatory EEG in adults with more severe dementia, which would be important in a post mortem study such as ours. Third, bulk RNA‐seq cannot distinguish between higher expression of reactive astrocyte genes due to more reactive astrocytes or increased gene expression without change in cell number.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory polysomnography, including EEG, could provide a more definitive differentiation of wake/sleep, provide additional information regarding sleep staging and depth, and identify some causes of sleep fragmentation (e.g., sleep apnea). While several studies have demonstrated the feasibility of ambulatory EEG in adults with mild dementia, 44,45 it remains challenging to obtain ambulatory EEG in adults with more severe dementia, which would be important in a post mortem study such as ours. Third, bulk RNA‐seq cannot distinguish between higher expression of reactive astrocyte genes due to more reactive astrocytes or increased gene expression without change in cell number.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cohort studies have investigated the association between sleep duration and cognitive disorders but had inconsistent results, such as the US Nurses’ Health Study by Tworoge et al ( 34 ), the Finnish Twin Cohort by Virta et al ( 35 ), and Screening Across the Lifespan Twin study by Bokenberger et al ( 36 ). Possible reasons included not large sample size ( n < 2,000), short follow-up period (<3 years), or weak in representativeness (e.g., only one sex or twin study).…”
Section: Discussionmentioning
confidence: 99%
“…Lucey et al investigated the relationship between cognitive performance and sleep duration measured by the single-channel EEG device, and showed that individuals with sleeping less than 4.5 or more than 6.5 h at night had declined cognitive scores (37). Because the sleep time is about one hour shorter measured by EEG than by self-reported, the results corresponded to 5.5-7.5 h per night of self-reported sleep time to have the lowest risk (34,37). Although the biological mechanisms of extreme sleep durations on cognition is still unclear, putative pathways included circadian dysfunction (38), increased accumulation of amyloid-β in the brain (39), and elevate levels of systemic inflammatory markers (e.g., C-reactive protein, interleukin-6) (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The current study is limited by the use of self‐report data, which can be impacted by recall inaccuracies. Subjective sleep measures, particularly of perceived sleep quality, have limited association with more objective sleep measures collected by actigraphy or polysomnography 30 and they do not capture key neurophysiological events integral for optimal sleep and which may provide greater insights into potential disease mechanisms. Additionally, our dataset did not capture obstructive sleep apnea, which is known to be prevalent in older people and linked to AD biomarkers and dementia risk 31 .…”
Section: Limitations and Future Directionsmentioning
confidence: 99%